A framing analysis of William A. Gamson on the news “The death of Yahya Sinwar” in France24 and Al-Hurroh - Nafiudin, Mukhammad; Basid, Abdul (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study aims to determine the framing patterns used by international media, especially France24 and Al-Hurroh, in reporting the conflict related to the death of one of Hamas' main leaders, Yahya Sinwar, due to Israeli airstrikes in Gaza. This research used a qualitative content analysis approach based on the framing theory developed by William A Gamson. The data were obtained from news articles that discussed the Sinwar death incident and Hamas' response to the event. The results of the analysis show that the framing devices in the reporting of Yahya Sinwar's death in both France24 and Al-Hurroh media consist of metaphors, catchphrases, examples, depictions, and visual images. In contrast, the reasoning device consists of a root, appeal to principle and consequences. The use of these framing and reasoning devices shows that in the reporting of Yahya Sinwar's death, there are differences in framing patterns that affect how information is conveyed and perceived. France24 frames events in a strategic and political context, while Al-Hurroh builds more fact-based narratives. The findings underscore the different framing approaches by the two media outlets that can influence readers' perceptions of the Hamas-Israel conflict and potentially shape public opinion and global policy on Middle East issues.